Experience in the management of patients with HTLV-1 positive adult T-cell leukemia/lymphoma in a Latin American center - Danielle Floyd-Aristizábal; Cristian Alonso Barreiro García; Oriana Arias-Valderrama; Catalina Proaño Millán; Nhora María Silva Perez; Joaquín Donaldo Rosales Martinez; Elizabeth Arrieta López (Therapeutic Advances in Hematology)
Background: Adult T-cell leukemia/lymphoma (ATL) is a neoplasm with a high prevalence in certain regions such as southwestern Japan, the Caribbean, sub-Saharan Africa, South America, and Australia. In Colombia, the seroprevalence of human T-cell lymphotropic virus type 1 (HTLV-1) has been reported in specific populations, but there is limited information about the clinical course and management of ATL in the country. Objectives: To describe the clinical characteristics, treatment patterns, and outcomes of patients diagnosed with HTLV-1-positive ATL in a high-complexity healthcare institution in Colombia and compare these findings with reports from other geographic regions. Design: Observational retrospective cohort study conducted in a single high-complexity healthcare institution in Cali, Colombia, including patients diagnosed between 2011 and January 2022. Methods: This study presents an observational retrospective cohort of patients diagnosed with HTLV-1-positive ATL and managed at a high-complexity institution in Cali, Colombia. Eligible patients were adults diagnosed with ATL and HTLV-1 seropositivity, receiving treatment between 2011 and January 2022. Demographic, clinical, and treatment-related variables were collected and analyzed using descriptive and survival analyses. Results: Thirty-three patients diagnosed with ATL between 2011, and January 2022 were identified and included in the study. Most patients were female (52%) with a median age of 54 years. Acute presentation was the most common (64%), and most patients were identified at Ann Arbor stage 4. Treatment mainly consisted of various chemotherapy protocols, with cyclophosphamide, doxorubicin hydrochloride, vincristine sulfate, and prednisone (CHOP)-like regimens being the most frequently used. However, the overall response rate to chemotherapy was low, and most patients experienced complications and toxicities associated with treatment. Conclusion: This study provides insights into the clinical course and management of ATL in a Colombian population. The findings highlight the predominance of acute presentations, advanced disease stages at diagnosis, and challenges in achieving a complete response with conventional chemotherapy. Further research is needed to improve treatment strategies, identify prognostic markers, and develop more effective therapies for ATL patients in Colombia.